Split (3x-4)/(x+2)(x-3) into partial fractions

(3x-4)/(x+2)(x-3) = A/(x+2) + B/(x-3)=> 3x-4 = A(x-3) + B(x+2)Let x = -2-10 = -5AA = 2Let x = 35 = 5BB = 1∴ (3x-4)/(x+2)(x-3) = 2/(x+2) + 1/(x-3)

Related Maths A Level answers

All answers ▸

Find the first derivative of 2x^3+5x^2+4x+1 (with respect to x)


Differentiate "sin(2x)"


If given two parametric equations for a curve, how would you work out an equation for the gradient?


Solve dy/dx= (x√(x^2+3))/e^2y given that y=0 when x=1, giving your answer in the form y = f(x)


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences